The impact of pregnancy rates of using two different cut-off levels for high serum estradiol levels on the day of the hCG injection: Results from the same cohort of patients with long down-regulated ART cycles - YOLDEMİR, AHMET TEVFİK (My University, 2013)
Objective: To determine, from a single cohort of patients whether on the day of the human chorionic gonadotropin (hCG) injection, two different cut-off levels for high serum estradiol (E2) levels affect pregnancy rates in long-down regulated assisted reproductive technology (ART) cycles. Patients and Methods: A retrospective cohort analysis was performed in a University affiliated hospital on 539 women undergoing consecutive in vitro fertilization/intacytoplasmic sperm injection (IVF/ICSI) treatment with long-down regulation and recombinant follicular stimulating hormone (FSH) injections. The cut-off level for high E2 concentration was calculated according to a centile analysis of E2 levels on the day of hCG administration. Women in group 1 were divided into subgroup A with E2 levels from the 25th to 75th centiles (1040-2500pg/ml) and subgroup B with E2 levels from the 75th to 100th centiles (>2500pg/ml), respectively. Women in group 2 were divided into subgroup A with E2 levels from the 10th to 90th centile (650-3100pg/ml) and subgroup B with E2 levels from the 90th to 100th centile (>3100pg/ml), respectively. The clinical pregnancy rates and ongoing pregnancy rates were compared. Results: The clinical pregnancy rates and ongoing pregnancy rates were similar in group 1 and group 2. Conclusion: High serum E2 levels on the day of the hCG injection day either set at 75th (2500pg/ml) or 90th percentiles (3100pg/ml) do not compromise pregnancy rates in cycles downregulated with gonadotropin-releasing hormone (GnRH) analogues. Key words: Gonadotropin-releasing analogue, Human chorionic gonadotropin, Pregnancy, long analogue cycle, Estradiol

Amaç: Yardımcı üreme teknikleri (YÜT) uygulanan hasta kohortunda insan koriyonik gonadotropin (hCG) günü oluşturulan iki farklı serum östradiol (E2) eşik değerlerinin YÜT gebelikleri üzerine etkilerinin araştırılması. Hastalar ve Yöntem: Üniversiteye bağlı eğitim hastanesinde uzun süreli gonadotropin salgılayıcı hormon baskısından sonra kullanılan rekombinant folikül stimüle edici hormon (FSH) ile YÜT tedavisi alan 539 ardışık kadın retrospektif analize alınmıştır. hCG günü alınan serum E2 seviyesinin yüksek eşik değeri persentil analizine göre yapılmıştır. Grup 1 için serum E2 seviyeleri 25– 75inci persentilde (1040-2500pg/ml)olanlar alt grup A ; serum E2 seviyeleri 75–100üncü persentilde (>2500pg/ml)olanlar alt grup B olarak ayrılmıştır. Grup 2 için serum E2 seviyeleri 10– 90ıncı persentilde olanlar(650-3100pg/ml) alt grup A ve serum E2 seviyeleri 90–100üncü persentilde (>3100pg/ml)olanlar alt grup B olarak ayrılmıştır. Klinik ve devam eden gebelik oranları karşılaştırılmıştır. Bulgular: Hem grup 1’de hem de grup 2’de klinik ve gebelik oranları benzerdir. Sonuç: hCG günü serum E2 seviyelerinin eşik değeri 75inci (2500pg/ml), veya 90ıncı persentil (3100pg/ml) üzerinde olması GnRH analogları ile baskılanmış uzun protokol YÜT sikluslarında gebelik oranlarını olumsuz etkilememektedir. Anahtar kelimeler: Gonadotropin salgılayıcı hormon analogu, İnsan korionik gonadotropin, Gebelik, Uzun analog siklusu, Östradiol
Aynı YÜT hasta kohortunda hCG günü oluşturulan iki farklı serum östradiol eşik değerlerinin YÜT gebelikleri üzerine etkileri
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & İÇECEK; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine